Pendekatan Muamalah dalam Mengatasi Tantangan Ekonomi Kontemporer - Ade Zuki Damanik (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This research aims to examine the application of muamalah principles in facing contemporary economic challenges. Using descriptive-analytical qualitative research methods, this study explores how muamalah, rooted in sharia law, can be a solution in addressing various modern economic issues, such as globalization, inequality, and technological change. The principles of muamalah, such as fair dealing, usury-free, as well as sustainable resource management, are examined in depth to demonstrate their relevance in contemporary economics. The research also discusses Islamic economic instruments such as zakat, infaq, sadaqah, waqf, and profit-sharing-based Islamic financial systems as tools to address inequality and promote economic inclusiveness. The results show that the application of muamalah is not only capable of supporting equitable and sustainable economic growth, but also offers solutions to global economic challenges. This research provides important theoretical insights for the development of sharia-based economic policies, with suggestions for further research focusing on empirical studies and applications of muamalah in local economic contexts..